Bentonite as eco‑friendly natural mineral support for Pd/CoFe2O4 catalyst applied in toluene diamine synthesis - Hatvani-Nagy Alpár Ferencz; Hajdu Viktória; Ilosvai Ágnes Mária; Muránszky Gábor; Sikora Emőke; Kristály Ferenc; Daróczi Lajos; Viskolcz Béla; Bela Fiser; Fiser Béla; Фішер Бейло; Vanyorek László (Springer Nature, 2024)
Abstract. Toluene diamine (TDA) is a major raw material in the polyurethane industry and thus, its production is highly important. TDA is obtained through the catalytic hydrogenation of 2,4-dinitrotoluene (2,4-DNT). In this study a special hydrogenation catalyst has been developed by decomposition cobalt ferrite nanoparticles onto a natural clay-oxide nanocomposite (bentonite) surface using a microwave-assisted solvothermal method. The catalyst particles were examined by TEM and X-ray diffraction. The palladium immobilized on the bentonite crystal surface was identified using an XRD and HRTEM device. The obtained catalyst possesses the advantageous property of being easily separable due to its magnetizability on a natural mineral support largely available and obtained through low carbon- and energy footprint methods. The catalyst demonstrated outstanding performance with a 2,4-DNT conversion rate exceeding 99% along with high yields and selectivity towards 2,4-TDA and all of this achieved within a short reaction time. Furthermore, the developed catalyst exhibited excellent stability, attributed to the strong interaction between the catalytically active metal and its support. Even after four cycles of reuse, the catalytic activity remained unaffected and the Pd content of the catalyst did not change, which indicates that the palladium component remained firmly attached to the magnetic support's surface.
https://www.nature.com/articles/s41598-024-54792-5#citeas
Editors: https://www.nature.com/srep/about/editors
Contents: https://www.nature.com/srep/research-articles?year=2024
Keywords: 2,4-DNT; Magnetic; Ferrite; Hydrogenation; Stability